Mastering JavaScript promises : discover and explore the world of promises, one of JavaScript's most powerful concepts - Hussain, Muzzamil (Community experience distilled., 2015)
This book is for all the software and web engineers wanting to apply the promises paradigm to their next project and get the best outcome from it. This book also acts as a reference for the engineers who are already using promises in their projects and want to improve their current knowledge to reach the next level. To get the most benefit from this book, you should know basic programming concepts, have a familiarity with JavaScript, and a good understanding of HTML.